Changes of hand preference in Parkinson's disease - Štochl, Jan; Croudace, Tim J; Brožová, Hana; Klempíř, Jiří; Roth, Jan; Růžička, Evžen (Journal of neural transmission (Vienna, Austria, 2012)
This study focused on the difference between pre-morbid and current hand preference of patients with Parkinson's disease (PD). A survey instrument comprised items measuring pre-morbid and current hand preference and question related to the side of occurrence of initial symptoms. These questions were administered to 471 PD patients. The results show a significant change of pre-morbid right hand preference toward using the left when the side of PD onset was on the right hand and vice versa. Disease duration does not predict the amount of hand preference shift.
Keywords: Surveys and Questionnaires; Humans; Functional Laterality; lidé středního věku; Female; Aged; senioři; lidé; Models, Statistical; reprodukovatelnost výsledků; průzkumy a dotazníky; ženské pohlaví; Data Interpretation, Statistical; funkční lateralita; Male; Reproducibility of Results; Middle Aged; Psychometrics; statistické modely; mužské pohlaví; psychometrie; Parkinson Disease; interpretace statistických dat; Parkinsonova nemoc